Web application for collection of biographic story graphs of PhD students - Pelikán, Jan; Svátek, Vojtěch, 1967 prosinec 1.-; Vencovský, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This master´s thesis aims to design a web application that enables students to save their doctoral study story through the designed application. The thesis deals with the development and functionality of the design of this application, developed for web browsers. Theoretical part outlines additional introduction to the whole topic, in depth explanation of all objectives and methods used to accomplish the objectives. The practical part of the thesis is description of the implementation, i.e., the actual development of the application and it´s designing. The empirical part of the thesis documents the user testing of the application with a summary of individual respondents report and findings, working as a recommendations for a future development of application.
Vedoucí práce: Vojtěch Svátek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: vývoj informačních systémů [obor dipl. práce]; diplomové práce; master's theses